Synthesis of a novel fluorescent amphiphilic chitosan biopolymer: photophysical and electrochemical behavior - Ozdal, Devrim; Asir, Suleyman; Bodapati, Jagadeesh B.; Icil, Huriye (Springernature, 2013)
The present investigation describes for the first time, the synthesis and detailed characterization of a novel fluorescent and amphiphilic chitosan polymer (3) containing fluorescent peryleneimide chromophores for biomedical applications. The polymer 3 is moderately soluble in a wide range of organic solvents and aqueous solutions, unlike chitosan (2). The M-w of 3 and 2 determined by GPC were 467 kDa and 460 kDa, respectively. The photophysical and electrochemical properties measured in solution and solid states are engrossing. 3 is soluble in the entire pH range and exhibits excimer emission above pH 5. In solution, 3 is electroactive but 2 is not. Whereas in the solid-state, 3 shows one quasi-reversible oxidation and reversible reduction step and 2 exhibits only one quasi-reversible oxidation step. Our results point out a new class of organic biopolymers that could yield promising potentials in many biomedical applications.
Keywords: Optical-Properties; Drug-Delivery; Perylene; Functionalization; Derivatives; Energy